2019
DOI: 10.1113/jp277565
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling purinergic regulation in the epididymis: activation of V‐ATPase‐dependent acidification by luminal ATP and adenosine

Abstract: Key points In the epididymis, elaborate communication networks between epithelial cells are important with respect to establishing an optimal acidic luminal environment for the maturation and storage of spermatozoa, which is essential for male fertility. Proton secretion by epididymal clear cells is achieved via the proton pumping V‐ATPase located in their apical membrane. In the present study, we dissect the molecular mechanisms by which clear cells respond to luminal ATP and adenosine to modulate their acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
(145 reference statements)
1
26
0
Order By: Relevance
“…In this manner, we found that proton secretion in CCs is activated by an elevation of luminal pH, which induces the trafficking of V‐ATPase‐containing vesicles from the apical pole to the plasma membrane. This results in the formation and elongation of numerous apical projections (Pastor‐Soler et al ., ; Beaulieu et al ., ; Park et al ., ; Battistone et al ., ). Based on their appearance on thin (5 μm) sections used for immunofluorescence labeling, we initially named these protrusions ‘microvilli’ (Breton et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In this manner, we found that proton secretion in CCs is activated by an elevation of luminal pH, which induces the trafficking of V‐ATPase‐containing vesicles from the apical pole to the plasma membrane. This results in the formation and elongation of numerous apical projections (Pastor‐Soler et al ., ; Beaulieu et al ., ; Park et al ., ; Battistone et al ., ). Based on their appearance on thin (5 μm) sections used for immunofluorescence labeling, we initially named these protrusions ‘microvilli’ (Breton et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…B; green), ‘activated’ CCs perfused at the alkaline pH of 7.8 had numerous microplicae labeled for the V‐ATPase and less intracellular reactivity (Fig. C; green; Pastor‐Soler et al ., ; Beaulieu et al ., ; Park et al ., ; Battistone et al ., ). Addition of bicarbonate, angiotensin II (ANGII), ATP, or adenosine to the luminal perfusate all induced the redistribution of V‐ATPase from intracellular vesicles to the apical membrane (Pastor‐Soler et al ., ; Beaulieu et al ., ; Shum et al ., ; Belleannee et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations